2012
DOI: 10.1093/toxsci/kfs233
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes: Bioenergetics and Utilization in Safety Screening

Abstract: Cardiotoxicity remains the number one reason for drug withdrawal from the market, and Food and Drug Administration issued black box warnings, thus demonstrating the need for more predictive preclinical safety screening, especially early in the drug discovery process when much chemical substrate is available. Whereas human-ether-a-go-go related gene screening has become routine to mitigate proarrhythmic risk, the development of in vitro assays predicting additional on- and off-target biochemical toxicities will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 33 publications
9
136
0
1
Order By: Relevance
“…Consequently, researchers have begun developing more relevant human model systems for high-throughput in vitro cardiotoxicity testing. As a monolayer or small multicellular aggregates, human pluripotent stem cell-derived CMs (hPSC-CMs) have been used in a wide range of analytical assays to assess the effect of drugs on various cardiobiological parameters: electrophysiology [4], calcium transients [5], contractility [6], cell movement (beating) [7], metabolic activity [8], morphology, and viability [9], alone or in combination [5,[7][8][9].…”
Section: Current Applications Of Human Cardiomyocytesmentioning
confidence: 99%
“…Consequently, researchers have begun developing more relevant human model systems for high-throughput in vitro cardiotoxicity testing. As a monolayer or small multicellular aggregates, human pluripotent stem cell-derived CMs (hPSC-CMs) have been used in a wide range of analytical assays to assess the effect of drugs on various cardiobiological parameters: electrophysiology [4], calcium transients [5], contractility [6], cell movement (beating) [7], metabolic activity [8], morphology, and viability [9], alone or in combination [5,[7][8][9].…”
Section: Current Applications Of Human Cardiomyocytesmentioning
confidence: 99%
“…Again, the mechanistic evaluation of cardiotoxicity in a beating model was crucial, as sunitinib was discovered to inhibit hERG as well as other cardiac ion channels in addition to potent cytotoxicity (37). hPSC-derived models of cardiac injury have shown that cardiac troponins and cardiac natriuretic peptides can be useful biomarkers of cardiac damage induced by chemotherapeutic agents (38), as can the release of troponin T and FABP3 (fatty acid-binding protein 3) following doxorubicin-induced cardiac necrosis (39) Using a variety of molecular markers, including mitochondrial membrane potential, endoplasmic reticulum integrity, Ca 2ϩ mobilization, and membrane permeability, combined with an assessment of cell viability, hPSC-derived cardiomyocytes were shown to be more predictive than primary dog cardiomyocytes and H9c2 cells when taking therapeutic concentration into consideration (40,41). Across a panel of cardiotoxic and non-cardiotoxic kinase inhibitors, mitochondrial dysfunction was identified as a critical component of injury of many of these compounds (40).…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…Although these cells are capable of spontaneous beating and show many physiological features of CMs, they remain immature. There are many features in which differences could be observed, including smaller cell size, different shape, different expression levels of ion channels as well as lower oxygen consumption levels and force development [5][6][7][8]. This immature physiology of iPSCderived CMs (iPSC-CMs) leads to differences in pharmacological response to many drugs tested thus far (including tetrodoxin, nisoldipine or lidocaine) [9].…”
Section: Introductionmentioning
confidence: 99%